Spectroscopic and chromatographic technique for forensic discrimination of marker pen inks - Ayathull Dhalayla Mohd. Jar, 1986-; Hanim Awab, supervisor; Wong, Kong Yong, supervisor; Fakulti Sains (2009)
Thesis (Sarjana Sains (Sains Forensik)) - Universiti Teknologi Malaysia, 2009